Analysis of Asset Selection in Alphabet Inc., Warner Bro., and Disney - Lien, Hauwei (Transactions on Economics, Business and Management Research, 2024)
This research analyzes three companies in different fields that are unique in their way. The three companies the research analyzed are Alphabet Inc., Warner Bros. Entertainment Inc., The Walt Disney. Alphabet Inc. is famous for its technology and digital services, especially online advertising. Warner Bro. focuses on media entertainment. Disney is a leading company that produces global entertainment with diverse revenue, including film production, theme parks, and streaming services. This research analyses these companies through three criteria: risk, profitability, and market ratio. This data shows why people should invest in these companies and what type of investors might be interested in investing. The innovation in AI that Alphabet owns attracts value and momentum investors looking for a stable stock with high growth. Warner Bro. has fewer types of investors that would in attracted due to its recent performance in the market. Disney attracts many PEG and index investors through its diverse revenue.